The Solar Particle Event on 10 September 2017 as observed onboard the International Space Station (ISS). Issue 9 (1st September 2018) - Berger, T.; Matthiä, D.; Burmeister, S.; Rios, R.; Lee, K.; Semones, E.; Hassler, D. M.; Stoffle, N.; Zeitlin, C.
Abstract: The nominal radiation environment in low Earth orbit, especially for the International Space Station (ISS), is dominated by two sources. The first is galactic cosmic radiation, which is modulated by the interplanetary and the Earth's magnetic fields, and the second is trapped radiation in the form of the Van Allen belts. The trapped radiation inside the ISS is mostly due to protons of the inner radiation belt. In addition to these sources sporadic solar particle events (SPEs) can produce high doses inside and outside the ISS, depending on the intensity and energy spectrum of the event. Before 2017, the last SPE observed inside the ISS with relevant radiation detectors occurred in May 2012. Even though we are currently approaching the next solar minimum, an SPE was observed in September 2017, which was (a) a ground‐level enhancement, (b) measured with various radiation detector systems onboard the ISS, and (c) observed on the surface of Mars. This paper gives an overview of the 10 September 2017 SPE measured with the DOSIS 3D‐DOSTEL and the ISS‐RAD (Radiation Assessment Detector) instruments, both located at this time in close proximity to each other in the Columbus Laboratory of the ISS. The additional dose received during the SPE was 146.2 μGy in Si as measured by ISS‐RAD and 67.8 μGy in Si as measured by the DOSIS 3D‐DOSTEL instruments. In comparison, the dose measured on the surface of Mars with the Mars Science Laboratory‐RAD instrument accounted to 418 μGy in Si. Plain Language Summary: Severe solar particle events can be the source for deterministic radiation effects on humans, commonly summarized under the term "radiation sickness." We examine the evolution of the solar particle event from 10 September 2017, which was the first event since May 2012 seen inside the International Space Station. Radiation dose values are provided by two instruments (DOSIS 3D‐DOSTEL and ISS‐RAD) positioned in close proximity to each other in the Columbus Laboratory. Key Points: A solar particle event—also seen as GLE 72 on Earth—was measured in September 2017 inside the International Space Station Data were provided by two detector systems, DOSIS 3D‐DOSTEL and ISS‐RAD, both in close proximity to each other in the Columbus Laboratory The additional absorbed dose due to the 10 September 2017 solar particle event was in the range of 67.8 to 146.2 μGy in Si